STUDY ON UPGRADING OF CONVENTIONAL CEMENT FOR ZONAL ISOLATION IN COALBED METHANE (CBM)WELLS BY USING FOAMEDCEMENT - MASHARIPOV, RUSLAN (2013)
Cementing gas wells in coalbed methane (CBM) formations can present a cementcirculation challenge because the coal formations tend to have low fracture gradients and break down under the hydrostatic pressure of the cement column. The use of conventional lightweight cement slurries and/or foam cement significantly increases the prospectof maintaining circulation throughout cement placement. However, wells with exceedingly low fracture gradients can suffer either partial or complete loss of circulation during cement placement even with lightweight slurries. Both conventional lightweight cement slurries and foam cements have restrictions. Conventional lightweight cement systems use low-density materials (i.e. hollow spheres, gilsonite) and high water-to-cement ratios as a means of reducing the equivalent circulating density (ECD).